New product development - Goffin, Keith (Henry Stewart Talks, 2012)
Why new product development (NPD) is crucial, Examples for new products, Why products fail, Examples: Caterpillar and citizen M, Key issues with managing new product development, The Pentathlon Framework, Customers' hidden needs, Stage-gate or phase review process, Cross-functional teams, Key tools and techniques for managing new product development, Kano model: features and satisfaction, Post-project reviews, Productivity of the NPD process